2009
DOI: 10.1038/sc.2009.65
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre study of the community needs of people with spinal cord injuries: the first 18 months

Abstract: Study design: Multi-centre, single cohort. Objectives: To assess the needs, perceived environmental barriers, level of participation and psychological function of spinal cord injured patients living in the community 3-18 months after discharge. Setting: The National Spinal Injuries Centre, Stoke Mandeville, UK.; Princess Royal Spinal Injuries Centre, Sheffield UK.; Midlands Centre for Spinal Injuries, Oswestry, UK. Method: Participants sustaining injury aged 18 or above were recruited from one of three spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 18 publications
8
38
1
Order By: Relevance
“…This reflects the way in which goals and expectations can change over 17 and lead individuals to re evaluate internal values and standards. The current study found that life satisfaction was unaffected by physical limitations, which supports previous qualitative findings 18 in which 51% of participants report other factors as contributing to life satisfaction. The sample recruited in the current study were recruited relatively early on in the rehabilitation process, and as previously discussed, the ability for personal goals and reevaluation of priorities is such that the predictive relationships found in the current study may not be extrapolated to individuals having lived with their injury over a longer period of time.…”
Section: Discussionsupporting
confidence: 91%
“…This reflects the way in which goals and expectations can change over 17 and lead individuals to re evaluate internal values and standards. The current study found that life satisfaction was unaffected by physical limitations, which supports previous qualitative findings 18 in which 51% of participants report other factors as contributing to life satisfaction. The sample recruited in the current study were recruited relatively early on in the rehabilitation process, and as previously discussed, the ability for personal goals and reevaluation of priorities is such that the predictive relationships found in the current study may not be extrapolated to individuals having lived with their injury over a longer period of time.…”
Section: Discussionsupporting
confidence: 91%
“…8 In acute tetraplegia, these deficits are likely to prolong rehabilitation, and in chronic tetraplegia these same deficits will reduce independence and limit vocational outcomes. 1,26 CPAP is poorly adhered to in people with tetraplegia, and as such alternative effective therapies are urgently needed. The identified, modifiable contributor to OSA of increased nasal resistance may present a therapeutic target for future research.…”
Section: Summary and Clinical Implicationsmentioning
confidence: 99%
“…9 Even more, SCI is a chronic illness and these patients encounter changing needs throughout their lives. 5 ToCUEST is offered as a training module.…”
Section: Modularmentioning
confidence: 99%
“…Literature stresses the importance of using clientcentered outcome measures in the assessment of persons with tetraplegia, but also the need to develop adaptable rehabilitation programs to ensure that individual requirements are addressed. 8,9 Also, a lack of theoretical frameworks to formalize client-centered rehabilitation approaches, 8,10 a lack of guidance on how to apply goal-setting theories into clinical practice 6 and the need to obtain evidence about their efficacy are reported. 7,11 Whereas some research in SCI focuses either on clientcenteredness and goal setting or on general training programs of arm and hand, both principles are merged in the present study.…”
Section: Introductionmentioning
confidence: 99%